AKUNTABILITAS KEBIJAKAN DALAM PELAKSANAAN PEMBANGUNAN FISIK RABAT JALAN DAN GEDUNG BUMDes (Studi di Desa Kasembon, Kecamata Kasembon, Kabupaten Malang) - Arum Manis; Hadiwiyono Hadiwiyono (JOURNAL AKSES STIA MALANG, 2022)
Public accountability is the task of agents (Government) to manage and report resources and disclose allactivities and activities related to the use of public resources to delegates. BUMDes by the Village Governmentof Kasenbon Maran Regency The type of research used in this study used a qualitative approach. ObjectivesUsing Data Collection Techniques The sampling technique used was secondary. The data analysis method usedin this study was an interactive data analysis model (interactive model) from Milles and Hubberman and Saldana.Development accountability pursued by the Palmdale Village Government is to involve variousstakeholders in the village's physical development plan, including those involved in the Palmdale Village Council,the Community, KPMD The Kasembon Village Government will support the six-stage infrastructure developmentin 2019, in accordance with the provisions and regulations which refers to Law Number 6 of 2014 concerningVillages to increase HR Accountability, most of the wars The next problem is that it is known that there is stillsufficient.Keywords : Policy Accountability in the Implementation of Physical Development of Road and BUMDes BuildingRebates by the Village Government